Efficacy evaluation with stratified randomized controlled study of foam dentifrice containing isodecyl galactosides in older adults - Iwawaki, Yuki; Goto, Takaharu; Kishimoto, Takahiro; Matsuda, Takashi; Fujimoto, Keiko; Nagao, Kan; Yoshimura, Kenji; Tajikara, Teppei; Eshita, Yoshiyuki; Yano, Yoshitaka; Ichikawa, Tetsuo (Journal of oral science, 2025)
Oral hygiene is mainly maintained by mechanical plaque removal, but this is often inadequate in older adults. Isodecyl galactosides (ID-Gal) inhibits bacterial co-aggregation and could promote the maintenance and improvement of oral hygiene. In this study, the efficacy of ID-Gal-containing foam dentifrice in oral hygiene among older adults was evaluated. Fifty-six subjects aged 65 years or older visited Tokushima University Hospital and were randomly assigned to interventions using ID-Gal-containing foam dentifrice applied to the dorsum of the tongue, or to controls using their usual dentifrice. Microbiological and clinical oral health parameters were evaluated before, and at 1 and 2 months after the intervention. The intervention group showed significant decreases in black pigment-producing bacteria on the dorsum of the tongue, Fusobacterium, and total bacterial counts on the mucosa below the denture base after 1 month. Additionally, the intervention group showed significant decrease in the Winkle Tongue Coating Index (WTCI) after 2 months. ID-Gal-containing foam dentifrice decreased the number of bacteria by suppressing plaque formation and contributed to a reduction in the number of bacteria on the tongue and the WTCI. Collectively, these results suggest that ID-Gal-containing foam dentifrice is effective in maintaining and improving oral hygiene.